2018
DOI: 10.1038/s41467-018-06302-1
|View full text |Cite|
|
Sign up to set email alerts
|

Large-scale transcriptome-wide association study identifies new prostate cancer risk regions

Abstract: Although genome-wide association studies (GWAS) for prostate cancer (PrCa) have identified more than 100 risk regions, most of the risk genes at these regions remain largely unknown. Here we integrate the largest PrCa GWAS (N = 142,392) with gene expression measured in 45 tissues (N = 4458), including normal and tumor prostate, to perform a multi-tissue transcriptome-wide association study (TWAS) for PrCa. We identify 217 genes at 84 independent 1 Mb regions associated with PrCa risk, 9 of which are regions wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
120
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 143 publications
(121 citation statements)
references
References 59 publications
(90 reference statements)
1
120
0
Order By: Relevance
“…whether or not SNPs are eQTLs) [17][18][19][20] . Application of these methods to eQTL and GWAS data has shown that many genes have eQTLs that colocalize with GWAS loci [6][7][8][9][10] and/or exhibit significant cis-genetic correlations between their expression and trait [11][12][13][14][15][16][21][22][23][24][25][26][27][28] , while also showing that eQTLs as a whole are significantly enriched for disease heritability [17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…whether or not SNPs are eQTLs) [17][18][19][20] . Application of these methods to eQTL and GWAS data has shown that many genes have eQTLs that colocalize with GWAS loci [6][7][8][9][10] and/or exhibit significant cis-genetic correlations between their expression and trait [11][12][13][14][15][16][21][22][23][24][25][26][27][28] , while also showing that eQTLs as a whole are significantly enriched for disease heritability [17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…To further illustrate the benefit of hJAM , we next considered the gene-prostate cancer risk association of two genes on chromosome 1q32.1, gene PM20D1 (Peptidase M20 Domain Containing 1) and gene NUCKS1 (Nuclear Casein Kinase and Cyclin Dependent Kinase Substrate 1). Both PM20D1 and NUCKS1 are protein coding genes and previous transcriptome studies have found a significant effect of both PM20D1 and NUCKS1 on the risk of prostate cancer among a European-ancestry population 34, 35 . Due to the close proximity of the two genes along the genome, there is a potential for a univariate approach to result in biased estimates.…”
Section: Data Examplesmentioning
confidence: 87%
“…Often, an implicated GWAS locus contains many genes. Common GWAS mapping techniques would assign the SNP association to the closest gene, however, this has been shown to be suboptimal [12][13][14] . After conditioning on the TWAS signal for each transcriptome-wide significant hit, most of the signal was explained by the expression of the conditioned gene.…”
Section: Discussionmentioning
confidence: 99%